1984
DOI: 10.1177/0148607184008006668
|View full text |Cite
|
Sign up to set email alerts
|

Hub Colonization as the Initial Step in an Outbreak of Catheter‐Related Sepsis Due to Coagulase Negative Staphylococci during Parenteral Nutrition

Abstract: A prospective study was carried out to determine the pathogenesis of coagulase negative staphylococci catheter-related sepsis during parenteral nutrition. Forty-three catheters were cultured by semiquantitative and quantitative methods. The skin around the puncture site was cultured at the time of catheter removal and three segments of the catheter were cultured apart: the hub, the proximal subcutaneous segment, and the tip. Skin cultures were negative (89%) or yielded different coagulase negative staphylococc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
75
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(75 citation statements)
references
References 19 publications
0
75
0
Order By: Relevance
“…8 They reported that the hub of a catheter was the most important source of catheter-related infections. 9 This hypothesis has been supported by several studies. [23][24][25][26] Consequently, we adopted the closed hub system for the catheter connection in our patients.…”
Section: Discussionmentioning
confidence: 61%
“…8 They reported that the hub of a catheter was the most important source of catheter-related infections. 9 This hypothesis has been supported by several studies. [23][24][25][26] Consequently, we adopted the closed hub system for the catheter connection in our patients.…”
Section: Discussionmentioning
confidence: 61%
“…3) (107). However, investigators from Barcelona, Spain, have suggested that this figure omits an additional route of catheterrelated infection: contamination of the catheter hub (45,99,175). In one study of 135 subclavian catheters, 14 (70%) of 20 episodes of bacteremia were thought to have originated from a contaminated hub, with secondary colonization of the catheter tip (99).…”
Section: Sources Of Microorganisms Causing Infusion-related Infectionsmentioning
confidence: 99%
“…Blood culture contamination rates are considerably increased due to hub colonization if the blood is withdrawn from central venous lines as opposed to by venipuncture. (3,16,26,(40)(41)(42)52) The purpose of the current retrospective case-control study was four fold. First, we desired to determine, over a period of 1 year, the rate of CoNS blood contamination and infection in a group of patients from a unit (adult oncology) with a high frequency of central lines and thus high contamination and infection rates.…”
mentioning
confidence: 99%